Sustaining Digital Faith: How Technology Impacts Religious Activities and Participation in the Digital Era - Md. Ishaque; Mahmudulhassan Mahmudulhassan; Muhammad Abuzar (Bulletin of Islamic Research, 2023)
The digital age has significantly transformed religious practices, presenting both opportunities and challenges for individuals and communities. This study examines the impact of technology on religiosity, focusing on the shift from traditional religious practices to digital formats. Using secondary data, the research explores how digital tools like online platforms and virtual communities have reshaped religious engagement and community building. Despite the benefits of accessibility, such as the convenience of attending services remotely and accessing religious resources online, challenges also emerge. These include misinformation, distractions, and the potential erosion of personal spiritual experiences, which can undermine the authenticity of religious practices. The findings suggest that while technology offers greater accessibility to religious resources, religious organizations and leaders must balance virtual engagement with maintaining the integrity of traditional spiritual practices. The study concludes with recommendations for integrating faith into the digital landscape while preserving the core values of spirituality. This includes promoting responsible use of technology, fostering virtual spaces that encourage meaningful engagement, and ensuring that digital tools serve as enhancements, not replacements, for authentic spiritual experiences.